Tryptophan metabolism via serotonin in human CSF of different brain sites using a new neuroendoscopic technique - Longatti, P.; Comai, S.; Perin, A.; Bertazzo, A.; Rizzo, V.; Ragazzi, E.; Costa, C.V.L.; Allegri, G. (International Congress series, 2007)
A new neuroendoscopic technique has permitted a precise and accurate exploration of all the cerebral ventricles, making possible the study of the CSF of the lateral ventricles and, above all, the CSF adjacent to the walls of the third ventricle in humans. The concentrations of tryptophan and its metabolites via serotonin were measured in the CSF of different sites of the cerebral cavity, in particular in the third ventricle. Patients affected with non-communicating hydrocephalus undergoing neuroendoscopic third ventriculostomy were enrolled in the study. As controls, subjects not suffering from any neurological disease, who underwent lumbar subarachnoid anaesthesia for minor surgical procedures, provided lumbar CSF, and patients affected by Chiari malformation provided cisternal and right ventricular CSF. Tryptophan concentration was higher in right ventricular CSF than in lumbar CSF. Serotonin (5-HT) was detectable in the CSF of the right ventricle of hydrocephalic individuals. 5-Hydroxyindoleacetic acid (5-HIAA) was higher in the right ventricular CSF than in the cisternal and lumbar CSF both in controls and hydrocephalic subjects. However, the 5-HIAA level was higher in the right ventricular and cisternal CSF in hydrocephalic individuals in comparison to controls. 5-HT presented the highest concentration in the pineal recess, whereas the highest amounts of 5-HIAA were found in the choroids plexus, third and right ventricles and the lowest in the pineal recess, subarachnoid space and intepeduncular cistern. Melatonin is more concentrated within the ventricles, in particular the third ventricle, and in the CSF pineal recess. The use of this neuroendoscopic technique in hydrocephalic patients provides new insight into the metabolic pathway of tryptophan via serotonin in the CSF.